Faculty use of the course management system (CMS) iLearn at the American University of Sharjah - Prescott, David (2013)
That course management systems (CMS) are relevant to higher education is beyond question. Tertiary institutions invest significant resources in developing CMS and promoting their use by faculty members. Considerable research has been undertaken with respect to cost-effectiveness, to the buy as opposed to build quandary and also to CMS product rating. Far fewer studies have been devoted to examining how course management systems are being used in higher education, whether such use is effective and what views the faculty members who use/do not use the technology have about such systems. The American University of Sharjah (AUS) has a strong commitment to CMS through investment in iLearn (Blackboard) as a future teaching and learning medium. This paper reports on initial findings from an investigation, conducted by a cross-disciplinary, cross-generational, research team of faculty, staff and students. The study seeks to gain a clear appreciation of how iLearn is being used at AUS and to recognize the faculty members’ opinions and perceptions of the CMS iLearn.